2019
DOI: 10.3390/w11071415
|View full text |Cite
|
Sign up to set email alerts
|

A Quantity–Quality Model to Assess the Effects of Source Control Stormwater Management on Hydrology and Water Quality at the Catchment Scale

Abstract: The vast development of urban areas has resulted in the increase of stormwater peak runoff and volume. Water quality has also been adversely affected. The best management practices (BMPs) and low impact development (LID) techniques could be applied to urban areas to mitigate these effects. A quantity–quality model was developed to simulate LID practices at the catchment scale using the US Environmental Protection Agency Storm Water Management Model (US EPA SWMM). The purpose of the study was to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 62 publications
2
31
0
Order By: Relevance
“…In particular, this research confirms and expands previous research on the retention of stormwater and the reduction of peak stormwater runoff using decentralized systems. Stormwater peak runoff reduction in Kuala Lumpur, Malaysia, using low impact development systems (LID) consisting of vegetated swale and rain garden could only be reduced by up to 19% (for rainfall of between 70 and 90 mm) and up to 27% (for rainfall of up to 70 mm) [42].…”
Section: Discussion Of Stormwater Retention and Infiltration Potentialsmentioning
confidence: 99%
“…In particular, this research confirms and expands previous research on the retention of stormwater and the reduction of peak stormwater runoff using decentralized systems. Stormwater peak runoff reduction in Kuala Lumpur, Malaysia, using low impact development systems (LID) consisting of vegetated swale and rain garden could only be reduced by up to 19% (for rainfall of between 70 and 90 mm) and up to 27% (for rainfall of up to 70 mm) [42].…”
Section: Discussion Of Stormwater Retention and Infiltration Potentialsmentioning
confidence: 99%
“…found that rainfall intensity was the primary influencing factor for water quantity concerns while the rain garden proportion impacted water quality. Rezaei et al (2019) also saw a positive impact on water quality from the implementation of LID. The model was most sensitive to the percent imperviousness as it significantly impacted runoff and peak flow.…”
Section: Annual Literature Reviewmentioning
confidence: 99%
“…Therefore, if the vulnerability of cities is caused by the short duration with the low return period, LIDs should be first considered, otherwise detention ponds should be given the priority. Rezaei et al [23] also demonstrates that detention ponds are the proper solution to the flood control for long durations. In this study, the effect of detention ponds for flood reduction did not perform very well because those ponds were allocated in the existing parks and schools of the study area and these spaces were already designed at the end of the drainage system.…”
Section: Influence Of Different Rainfall Durations On Lid and Detentimentioning
confidence: 99%